The Impact of Mobile Legends Games on Student Learning Motivation: The Role of Parents and Teachers - Rochmayanti, Sri (Prosiding University Research Colloquium, 2021)
The advancement of technology is accelerating. Beginning with telecommunications technology, the internet, and intelligent computer-based technology. Until the first cell phones were used to fulfill communication needs, cellphones could only be used to do a few things, such as easily finding any information all over the world, playing online games from anywhere, and so on. Mobile Legends games are extremely popular. Not only do teenage boys enjoy playing these online games, but so do many girls. The goal of this study was to determine the impact of Mobile Legends game addiction on students' learning motivation, as well as the role of parents and teachers. This is a type of library research. The data used in the study was analyzed using data reduction, data display, and drawing conclusions. Reading and recording important information contained in various journals related to the research being conducted are data collection techniques. It is expected that the results of this study can be used as insights, references, and basic and consideration for future researchers in order to become other research areas whose topics are relevant to this study.